Analysis of the Influence of Digital Marketing Content on Customer Satisfaction at PT Godongijo Asri - Tua Manalu, Doni Sahat; Wicaksono, Aditya; Nurlaili, Ulil Azmi; Suharno, Suharno; Sari, Melani Permata; Bunda, Asti Permata; Kamila, Farhana Talida (International Journal of Economics (IJEC), 2025)
This research aims to analyze the influence of digital marketing content on customer satisfaction at PT Godongijo Asri, a tourist destination consisting of ecotainment education, restaurants and fishing lake. By involving 100 respondents, this research used the SWOT analysis method and Importance Performance Analysis (IPA) to evaluate the quality of digital marketing content and its impact on customer perception and satisfaction. The research results show that interesting and informative content can increase customer satisfaction. In addition, the company's internal analysis shows that PT Godongijo Asri is in Region I (Grow and Build) in the IE Matrix, which recommends growth and development strategies. Priority strategies include using brand awareness to create engaging content and diversifying content across various digital platforms. Even though many attributes are considered good, there are several aspects that need to be improved, such as clarity of information and website loading speed. In conclusion, digital marketing content has a significant influence on customer satisfaction, and companies are advised to continue to improve the quality of content and carry out regular updates to attract more customers.